Gamma Knife radiosurgery as salvage therapy for gangliogliomas after initial microsurgical resection. (October 2021) - Tuleasca, Constantin; Peciu-Florianu, Iulia; Enora, Vauleon; Reyns, Nicolas
Highlights: Gangliogliomas (GG) are considered WHO grade I tumors. Here, we present a series of GG who received Gamma Knife radiosurgery after initial microsurgery. The median follow-up after GKR was 54 months (mean 58.5, 6–120). The median marginal dose was 18 Gy (mean 17.5, 16–18). The median target volume was 0.5 mL (mean 0.904, 0.228–2.3). The median prescription isodose volume was 0.6 mL (mean 0.9, 0.3–2.4). Abstract: Introduction: Gangliogliomas (GG) are considered WHO grade I rare tumors. While they commonly manifest as temporal lobe epilepsy, they can be located anywhere in the brain. Primary treatment is complete microsurgical resection. Remnant or recurrent GG can benefit from radiation therapy. Here, we present a series of GG who received Gamma Knife radiosurgery (GKR) after initial microsurgery. Methods: Between October 2009 and February 2020, four patients benefitted from such approach. The median age at surgery was 16 years (mean 17, 11–25) and at the time of GKR was 22.5 years (mean 23, 19–28). Initial clinical symptom was epilepsy in 3 cases and incidental in one. Biopsy was firstly performed in one case. One patient had stereotactic electroencephalography. The respective anatomical locations were right parieto-occipital, sylvian, left paraventricular and left inferior parietal. Results: Gamma Knife radiosurgery was performed after a median time of 3.5 years after initial gross total microsurgical resection (GTR). The median follow-up after GKR was 54 months (mean 58.5, 6–120). The median marginal dose was 18 Gy (mean 17.5, 16–18). The median target volume was 0.5 mL (mean 0.904, 0.228–2.3). The median prescription isodose volume was 0.6 mL (mean 0.9, 0.3–2.4). At last follow-up, GG majorly decreased in 3 patients, remained stable in one. Conclusion: Gamma Knife radiosurgery is safe and effective for remnant GG after GTR. Primary treatment remains microsurgical resection, especially in cases with symptomatic mass effect or with epilepsy. Single fraction GKR can be a valuable option for remnant or recurrent tumors after initial resection.